ANALISIS KEBUTUHAN KOMPETENSI KEPALA SEKOLAH DALAM MENGELOLA ADMINISTRASI PENDIDIKAN ANAK USIA DINI - Septia Putri Anggraini; Armanila Armanila; Fadiza Syafira Nasution; Maghfirah Maghfirah; Elfina Yanti Siregar (CV. ADIBA AISHA AMIRA, 2023)
This journal aims to analyze the competency needs of school principals in managing the administration of early childhood education at Al-Ikhlasiyah Kindergarten. Early childhood education plays an important role in shaping children's early development. Therefore, the role of school principals in ensuring effective educational administration is crucial. The research method used was descriptive analysis with a qualitative approach, with data collected through in-depth interviews with school principals from various early childhood education institutions. The results of the analysis identified a number of key competencies required by school principals, including leadership that is sensitive to children's needs, management of human, financial and material resources, strong communication skills, interpersonal skills, creativity and community involvement. Child-oriented leadership at Al-Ikhlasiyah Kindergarten emphasizes the interests and needs of children as the main priority, with a focus on the optimal growth and development of each child. Leaders at this institution understand the characteristics and developmental needs of early childhood, encourage an exploratory learning approach, focus on developing social and emotional skills, and ensure parent and community involvement. Through this approach, Al-Ikhlasiyah Kindergarten ensures the best educational experience for children, forms a strong foundation for further development, and helps them grow into talented individuals who contribute positively to society.